SELF-AWARENESS OF THE INDIVIDUAL IN THE INTERPRETATION OF WESTERN PSYCHOLOGISTS, ACTIVITY AND ORIENTATION - M. Soipova (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the definition of a person’s activity in a more general form, in the form of a combination, is expressed in his ideological principles, in the consistent defense of his point of view, and in the unity of his words and deeds.